THE DEPARTMENT OF HIGHWAYS AND AERODROMES IN THE CONSTRUCTION OF THE ROAD SYSTEM IN THE REPUBLIC OF SAKHA (YAKUTIA) - Nikolay M. Makarov (Высшее образование в России)
The article discusses the topical problem concerning the development of road network in Sakha Republic. Due to the vast territory of the region, its socio(economic development largely depends on the efficient functioning of the transportation system. The article briefly dwells on the participation of Road Faculty of the North-Eastern Federal University in solving the task of road construction in the region.